X-SRL dataset and mBERT word aligner - Daza, Angel (Universität, 2021)
This code contains a method to automatically align words from parallel sentences by using multilingual BERT pre-trained embeddings. This can be used to transfer source annotations (for example labeled English sentences) into the target side (for example a German translation of the sentence) by transferring the label into the best-aligned target word. This newly labeled data can be used to train different multilingual SOTA models to improve performance, especially for the lower-resource languages.
Kind of data: Program source code
Gesehen am 18.02.2021
Keywords: Forschungsdaten; Datenbank